Preparation method of double-frequency optical thin film capable of reflecting 1064nm wavelength and simultaneously transmitting 7.7-10.5 mu m wave band by zinc sulfide substrate

By using YbF3 and ZnSe film materials on the zinc sulfide substrate to construct an alternating multilayer film structure, the problem of insufficient optical performance in the 1064nm wavelength and 7.7-10.5μm band in the prior art is solved, and high reflectivity and high transmittance are achieved. And meet the acceptance standards of GJB2485A-2019.

CN119265511APending Publication Date: 2025-01-07安徽光智科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411279963.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a zinc sulfide-based optical film with high reflectivity at a wavelength of 1064nm and a high transmittance in the 7.7-10.5μm band, and it cannot meet the acceptance standards of GJB2485A-2019.

Method used

Using two films, YbF3 and ZnSe, an alternating multi-layer film structure is formed on the zinc sulfide substrate. Through ion source-assisted deposition, a high-reflective film system and an urgency film system are constructed to ensure that the first and second sides of the lens are both. Achieve efficient optical performance.

Benefits of technology

It achieved high reflectivity (more than 99%) at 1064nm wavelength and high transmittance (more than 97.3%) in the 7.7-10.5μm band, and comply with the acceptance standards of GJB2485A-2019.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119265511A_ABST
    Figure CN119265511A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of a double-frequency optical thin film with a zinc sulfide substrate reflecting 1064nm wavelength and transmitting 7.7-10.5 [mu] m wave band. The preparation method comprises the following steps: S1, cleaning and preparing materials; s2, vacuumizing, baking and pre-melting; s3, ion source cleaning; s4, plating a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer, a sixth ZnSe film layer, a seventh YbF3 film layer, an eighth ZnSe film layer, a ninth YbF3 film layer, a tenth ZnSe film layer, an eleventh YbF3 film layer, a twelfth ZnSe film layer, a thirteenth YbF3 film layer, a fourteenth ZnSe film layer, a fifteenth YbF3 film layer, a sixteenth ZnSe film layer and a seventeenth YbF3 film layer on the first surface under vacuum; the eighteenth ZnSe film layer is assisted by an ion source; s5, keeping at constant temperature after plating; s6, cooling and part taking; s7, repeating the steps S1 to S3; s8, plating a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer and a sixth ZnSe film layer on the second surface under vacuum, and assisting by an ion source; and S9, repeating the steps S5 and S6.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the field of infrared coating technology, and more specifically to a method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a 1064 nm wavelength and transmits a 7.7-10.5 μm band. Background Art Summary of the invention

[0002] In view of the problems existing in the background technology, an object of the present disclosure is to provide a method for preparing a dual-frequency optical film with a zinc sulfide substrate that reflects a wavelength of 1064nm and transmits a wavelength of 7.7-10.5μm, which can be used to achieve high reflectivity at a wavelength of 1064nm and high transmittance in the wavelength band of 7.7-10.5μm.

[0003] Another object of the present disclosure is to provide a method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm, which can comply with GJB2485A-2019 acceptance.

[0004] Thus, a preparation method of a dual-frequency optical film with a zinc sulfide substrate that reflects a wavelength of 1064nm and transmits a wavelength of 7.7-10.5μm comprises the following steps: S1, before plating, cleaning the accompanying plating sheet and product of the zinc sulfide substrate as the lens and preparing two kinds of film materials, YbF3 and ZnSe; S2, placing the cleaned lens into a fixture, hanging the fixture with the lens in place into the cavity of a coating machine, vacuum baking and pre-melting the film material; S3, cleaning the lens with an ion source; S4, coating the first YbF3 film layer, the second ZnSe film layer, the third YbF3 film layer, the fourth ZnSe film layer, the fifth YbF3 film layer, the sixth ZnSe film layer, the seventh YbF3 film layer, the eighth ZnSe film layer, the ninth YbF3 film layer and the tenth ZnSe film layer in sequence on the first surface of the lens under vacuum conditions. Se film layer, eleventh YbF3 film layer, twelfth ZnSe film layer, thirteenth YbF3 film layer, fourteenth ZnSe film layer, fifteenth YbF3 film layer, sixteenth ZnSe film layer, seventeenth YbF3 film layer, eighteenth ZnSe film layer, eighteen film layers constitute a high reflective film system, and all eighteen film layers are deposited with the assistance of an ion source; S5, maintain constant temperature after plating; S6, cool and take out the piece; S7, repeat steps S1 to S3; S8, under vacuum conditions, on the second surface of the lens, successively plate the first YbF3 film layer, the second ZnSe film layer, the third YbF3 film layer, the fourth ZnSe film layer, the fifth YbF3 film layer, and the sixth ZnSe film layer, the six film layers constitute an anti-reflection film system, and all six film layers are deposited with the assistance of an ion source; S9, repeat steps S5 and S6.

[0005] The beneficial effects of the present disclosure are as follows.

[0006] In the preparation method of the dual-frequency optical film of the zinc sulfide substrate reflecting 1064nm wavelength and transmitting 7.7-10.5μm band according to the present disclosure, by using two film materials of YbF3 and ZnSe, YbF3 and ZnSe form the first to eighteenth layers (i.e. (LH)) alternately on the first surface p , p=9, L represents low refractive index YbF3, H represents high refractive index ZnSe) composed of a high reflective film system, YbF3 and ZnSe form alternating first to sixth layers on the second surface (i.e. (LH) q , q = 3, L represents low refractive index YbF3, H represents high refractive index ZnSe), as verified by the test process, can be used to achieve high reflectivity at 1064nm wavelength and high transmittance in the 7.7-10.5μm band, for example, the reflectivity at 1064nm wavelength is more than 99%, and the average transmittance in the 7.7-10.5μm band is more than 97.3%

[0007] In the preparation method of the dual-frequency optical film that reflects 1064nm wavelength and transmits 7.7-10.5μm band on the zinc sulfide substrate disclosed in the present invention, by adopting two film materials, YbF3 and ZnSe, by adopting two film materials, YbF3 and ZnSe form alternating first to eighteenth layers on the first surface and the first to eighteenth layers are all deposited using an ion source, and YbF3 and ZnSe form alternating first to sixth layers on the second surface and the first to sixth layers are all deposited using an ion source. It can meet the acceptance of GJB2485A-2019. BRIEF DESCRIPTION OF THE DRAWINGS

[0008] Figure 1 It is a schematic structural diagram of a method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to the present disclosure.

[0009] Figure 2 It is a reflectivity curve at 1064nm of the dual-frequency optical film coated with the accompanying coating sheet of Example 1, which reflects 1064nm wavelength and transmits 7.7-10.5μm band.

[0010] Figure 3 It is a transmittance curve in the 7.7-10.5 μm band of the dual-frequency optical film coated with the accompanying coating sheet of Example 1, which reflects the 1064 nm wavelength and transmits the 7.7-10.5 μm band.

[0011] Figure 4 This is a reflectivity curve at 1064nm of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 2, which is plated on both sides of the accompanying plate.

[0012] Figure 5 It is a transmittance curve diagram of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of Example 2, which is plated on both sides of the accompanying plate with zinc sulfide substrate in the 7.7-10.5μm band.

[0013] Figure 6 This is a reflectivity curve at 1064nm of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 3, which is plated on both sides of the accompanying plate.

[0014] Figure 7 It is a transmittance curve diagram of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of Example 3, which is plated on both sides of the accompanying plate with zinc sulfide substrate in the 7.7-10.5μm band.

[0015] Figure 8 It is a reflectivity curve of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 1 coated on both sides of the accompanying coating sheet at a wavelength of 1064nm.

[0016] Fig. 9 It is a transmittance curve of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of the accompanying coating sheet of comparative example 1, which is coated on both sides of the zinc sulfide substrate in the 7.7-10.5μm band.

[0017] Fig.10 This is a reflectivity curve of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 2, which is plated on both sides of the accompanying plate.

[0018] Fig.11 It is a transmittance curve of the 7.7-10.5 μm band antireflection film system of the 1064 nm wavelength high-reflection 7.7-10.5 μm band of the accompanying coating sheet of Example 2, which is plated on both sides of the zinc sulfide substrate.

[0019] Fig.12 This is a reflectivity curve of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 3, which is plated on both sides of the accompanying coating sheet with zinc sulfide substrate.

[0020] Fig.13 It is a transmittance curve of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of the accompanying coating sheet of comparative example 3, which is coated on both sides of the zinc sulfide substrate in the 7.7-10.5μm band. DETAILED DESCRIPTION

[0021] It will be understood that the disclosed embodiments are merely examples of the present disclosure, which may be implemented in various forms, and therefore, the specific details disclosed herein should not be interpreted as limiting, but merely as a basis for the claims and as a representative basis for teaching one of ordinary skill in the art to implement the present disclosure in various ways.

[0022] [Preparation method of dual-frequency optical film with zinc sulfide substrate that reflects 1064nm wavelength and transmits 7.7-10.5μm wavelength]

[0023] The preparation method of the dual-frequency optical film of the zinc sulfide substrate according to the present disclosure, which reflects 1064 nm wavelength and transmits 7.7-10.5 μm wavelength, comprises the following steps:

[0024] S1, before plating, clean the accompanying plating sheet and products of the zinc sulfide substrate as the lens and prepare the two film materials of YbF3 and ZnSe;

[0025] S2, the cleaned lens is placed in a fixture, and the fixture with the lens is hung in the cavity of the coating machine for vacuum baking and pre-melting of the film material;

[0026] S3, ion source cleaning lens;

[0027] S4, under vacuum conditions, on the first surface of the lens, a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer, a sixth ZnSe film layer, a seventh YbF3 film layer, an eighth ZnSe film layer, a ninth YbF3 film layer, a tenth ZnSe film layer, an eleventh YbF3 film layer, a twelfth ZnSe film layer, a thirteenth YbF3 film layer, a fourteenth ZnSe film layer, a fifteenth YbF3 film layer, a sixteenth ZnSe film layer, a seventeenth YbF3 film layer, and an eighteenth ZnSe film layer are deposited in sequence, the eighteen film layers forming a high-reflection film system, and the eighteen film layers are all deposited using an ion source as an auxiliary.

[0028] S5, constant temperature maintenance after plating;

[0029] S6, cooling and picking up;

[0030] S7, repeating steps S1 to S3;

[0031] S8, under vacuum conditions, sequentially depositing a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer, and a sixth ZnSe film layer on the second surface of the lens, wherein the six film layers constitute an antireflection film system, and the six film layers are all deposited using an ion source to assist deposition;

[0032] S9, repeat step S5 and step S6.

[0033] In the preparation method of the dual-frequency optical film of the zinc sulfide substrate reflecting 1064nm wavelength and transmitting 7.7-10.5μm band according to the present disclosure, by using two film materials of YbF3 and ZnSe, YbF3 and ZnSe form the first to eighteenth layers (i.e. (LH)) alternately on the first surface p , p=9, L represents low refractive index YbF3, H represents high refractive index ZnSe) composed of a high reflective film system, YbF3 and ZnSe form alternating first to sixth layers on the second surface (i.e. (LH) q , q = 3, L represents low refractive index YbF3, H represents high refractive index ZnSe), as verified by the test process described later, can be used to achieve high reflectivity at 1064nm wavelength and high transmittance in the 7.7-10.5μm band, for example, the reflectivity at 1064nm wavelength is more than 99%, and the average transmittance in the 7.7-10.5μm band is more than 97.3%

[0034] In the preparation method of the dual-frequency optical film that reflects 1064nm wavelength and transmits 7.7-10.5μm band on the zinc sulfide substrate disclosed in the present invention, by adopting two film materials, YbF3 and ZnSe, by adopting two film materials, YbF3 and ZnSe form alternating first to eighteenth layers on the first surface and the first to eighteenth layers are all deposited using an ion source, and YbF3 and ZnSe form alternating first to sixth layers on the second surface and the first to sixth layers are all deposited using an ion source. It can meet the acceptance of GJB2485A-2019.

[0035] The cleaning in step S1 is beneficial to improving the surface state of the first surface and the second surface of the lens, removing surface contaminants, ensuring the cleanliness before coating, ensuring that there will be no interference from impurities during the coating process, and helping to improve the bonding performance of the corresponding film system on each surface with the corresponding surface of the lens, and improving the flatness of the film layer. For example, in step S1, the cleaning is carried out by ultrasonic cleaning and manual wiping. For example, the thickness of the accompanying coating sheet is 1.0 mm.

[0036] The baking in step S2 prepares the temperature for pre-melting the film material. Pre-melting the film material can release the gas in the film material and remove the impurities in the film material to ensure the purity of the film material, thereby reducing the adverse factors that affect the quality of the film layer during the film coating process in steps S4 and S8. In addition, baking also heats the lens. In one example, in step S2, the temperature of the chamber of the coating machine is set to 150°C; when the vacuum reaches (3.0-5.0)×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 15-20 minutes.

[0037] The ion source cleaning in step S3 uses ion bombardment to clean the surface microstructure of the lens, which can eliminate the oxide layer on the surface of the lens, making the surface of the lens cleaner and conducive to the firm adhesion and growth of the film layer. In one example, in step S3, when the vacuum degree reaches (1.0-2.0)×10 -3 Pa, start the ion source of the vacuum coating machine, and set the ion cleaning parameters of the ion source as follows: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 220V, anode current 2A, argon flow rate in neutralization gas 100%, and cleaning time 250-350s.

[0038] In one example, in step S4 and step S8, argon gas is filled into the chamber of the coating machine to form a flowing vacuum during coating, ensuring that the coating vacuum is maintained at (4.5-5.5)×10 -3 Pa, and maintain the coating temperature at 150°C.

[0039] In one example, in step S4 and step S8, the evaporation mode of the film material is: both YbF3 and ZnSe are evaporated using resistance heating.

[0040] In one example, in step S4 and step S8, the deposition rate of the film material is: the deposition rate of the YbF3 film layer is The deposition rate of ZnSe film is

[0041] In one example, in step S4,

[0042] The thickness of the first YbF3 film is 171.42±3nm.

[0043] The thickness of the second ZnSe film is 341.29±3nm.

[0044] The thickness of the third YbF3 film is 215.73±3nm.

[0045] The thickness of the fourth ZnSe film is 84.31±3nm.

[0046] The thickness of the fifth YbF3 film is 235.46±3nm.

[0047] The thickness of the sixth ZnSe film layer is 320.79±3nm.

[0048] The thickness of the seventh YbF3 film is 878.52±3nm.

[0049] The thickness of the eighth ZnSe film layer is 150.83±3nm.

[0050] The thickness of the ninth YbF3 film is 141.02±3nm.

[0051] The thickness of the tenth ZnSe film is 352.72±3nm.

[0052] The thickness of the eleventh YbF3 film layer is 214.99±3nm.

[0053] The thickness of the twelfth ZnSe film is 95.59±3nm.

[0054] The thickness of the thirteenth YbF3 film layer is 208.44±3nm.

[0055] The thickness of the fourteenth ZnSe film layer is 369.79±3nm.

[0056] The thickness of the fifteenth YbF3 film is 95.67±3nm.

[0057] The thickness of the sixteenth ZnSe film layer is 597.16±3nm.

[0058] The thickness of the seventeenth YbF3 film layer is 1316.55±3nm.

[0059] The thickness of the eighteenth ZnSe film layer is 100.98±3nm;

[0060] In step S8,

[0061] The thickness of the first YbF3 film is 120.00±3nm.

[0062] The thickness of the second ZnSe film is 910.06±3nm.

[0063] The thickness of the third YbF3 film is 223.53±3nm.

[0064] The thickness of the fourth ZnSe film is 910.91±3nm.

[0065] The thickness of the fifth YbF3 film is 114.25±3nm.

[0066] The thickness of the sixth ZnSe film layer is 116.49±3nm;

[0067] In step S4 and step S8, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the new crystal oscillator pieces among the multiple crystal oscillator pieces to work accordingly, and the crystal oscillator frequency is not less than 6 MHz.

[0068] In one example, in step S4 and step S8, the ion source parameters when depositing the YbF3 film are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 130V, anode current 1.3A, argon flow rate in the neutralization gas is 30%, and oxygen flow rate in the neutralization gas is 70%; the ion source parameters when depositing the ZnSe film are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1A, and argon flow rate in the neutralization gas is 100%.

[0069] In one example, in step S5, after plating is completed, the chamber is kept at a constant temperature of 150°C for 5-15 minutes.

[0070] In one example, in step S6, the door is opened to take out the items when the temperature drops below 100°C.

[0071] [test]

[0072] Example 1

[0073] The preparation method of the dual-frequency optical film of Example 1 that reflects 1064 nm wavelength and transmits 7.7-10.5 μm wavelength on the zinc sulfide substrate is as follows:

[0074] S1, before plating, ultrasonic cleaning is used for the accompanying plating sheet and products of the zinc sulfide substrate of the lens, and the YbF3 and ZnSe film materials are prepared. The thickness of the accompanying plating sheet is 1.0mm;

[0075] S2, the cleaned lens is placed in the fixture, and the fixture with the lens is hung in the cavity of the coating machine, vacuum baking and pre-melting of the film material. The coating machine is a vacuum coating machine with a Hall ion source with a neutralizer manufactured and sold by Chengdu Xiwoke Vacuum Technology Co., Ltd. The Hall ion source with a neutralizer is purchased from Boton Optoelectronics Technology Co., Ltd. The temperature of the cavity of the coating machine is set to 150°C. When the vacuum reaches 4.0×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 20 minutes.

[0076] S3, ion source cleaning lens, when the vacuum reaches 1.5×10 -3 Pa, start the ion source of the vacuum coating machine, and set the ion cleaning parameters of the ion source as follows: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 220V, anode current 2A, argon flow rate in neutralization gas 100%, and cleaning time 300s;

[0077] S4, under vacuum conditions, on the first surface of the lens, a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer, a sixth ZnSe film layer, a seventh YbF3 film layer, an eighth ZnSe film layer, a ninth YbF3 film layer, a tenth ZnSe film layer, an eleventh YbF3 film layer, a twelfth ZnSe film layer, a thirteenth YbF3 film layer, a fourteenth ZnSe film layer, a fifteenth YbF3 film layer, a sixteenth ZnSe film layer, a seventeenth YbF3 film layer, and an eighteenth ZnSe film layer are deposited in sequence, the eighteen film layers forming a high-reflection film system, and the eighteen film layers are all deposited using an ion source as an auxiliary.

[0078] S5, after plating is completed, the cavity is kept at a constant temperature of 150°C for 10 minutes;

[0079] S6, wait until the temperature drops to 100°C, open the door and take out the items;

[0080] S7, repeating steps S1 to S3;

[0081] S8, under vacuum conditions, sequentially depositing a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer, and a sixth ZnSe film layer on the second surface of the lens, wherein the six film layers constitute an antireflection film system, and the six film layers are all deposited using an ion source to assist deposition;

[0082] S9, repeating steps S5 and S6;

[0083] Among them, in step S4 and step S8,

[0084] During coating, argon gas is filled into the chamber of the coating machine and evacuated to form a flowing vacuum to ensure that the vacuum degree of the coating is maintained at 5.0×10 -3 Pa, and maintain the coating temperature at 150°C;

[0085] Both YbF3 and ZnSe are evaporated using resistance heating;

[0086] The deposition rate of the YbF3 film is The deposition rate of ZnSe film is

[0087] The crystal oscillator method is used to monitor the film thickness by using the corresponding crystal oscillator of the multiple crystal oscillators of the crystal controller. After the ion source is cleaned, the crystal controller controls the corresponding operation of the new crystal oscillator of the multiple crystal oscillators, and the crystal oscillator frequency is 6MHz;

[0088] The ion source parameters when depositing the YbF3 film layer are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 130V, anode current 1.3A, argon flow rate in neutralization gas 30%, oxygen flow rate in neutralization gas 70%;

[0089] The ion source parameters when depositing the ZnSe film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1A, and argon gas flow rate in the neutralization gas is 100%;

[0090] Among them, in step S4,

[0091] The thickness of the first YbF3 film is 171.42nm.

[0092] The thickness of the second ZnSe film is 341.29nm.

[0093] The thickness of the third YbF3 film is 215.73nm.

[0094] The thickness of the fourth ZnSe film is 84.31nm.

[0095] The thickness of the fifth YbF3 film is 235.46nm.

[0096] The thickness of the sixth ZnSe film is 320.79nm.

[0097] The thickness of the seventh YbF3 film is 878.52nm.

[0098] The thickness of the eighth ZnSe film layer is 150.83nm.

[0099] The thickness of the ninth YbF3 film is 141.02nm.

[0100] The thickness of the tenth ZnSe film layer is 352.72nm.

[0101] The thickness of the eleventh YbF3 film layer is 214.99nm.

[0102] The thickness of the twelfth ZnSe film is 95.59nm.

[0103] The thickness of the thirteenth YbF3 film layer is 208.44nm.

[0104] The thickness of the fourteenth ZnSe film layer is 369.79nm.

[0105] The thickness of the fifteenth YbF3 film layer is 95.67nm.

[0106] The thickness of the sixteenth ZnSe film layer is 597.16nm.

[0107] The thickness of the seventeenth YbF3 film layer is 1316.55nm.

[0108] The thickness of the eighteenth ZnSe film layer is 100.98nm;

[0109] Among them, in step S8,

[0110] The thickness of the first YbF3 film is 120.00nm.

[0111] The thickness of the second ZnSe film is 910.06nm.

[0112] The thickness of the third YbF3 film is 223.53nm.

[0113] The thickness of the fourth ZnSe film is 910.91nm.

[0114] The thickness of the fifth YbF3 film is 114.25nm.

[0115] The thickness of the sixth ZnSe film layer is 116.49 nm.

[0116] Example 2

[0117] Except for the vacuum degree of 3.0×10 -3 Pa, the vacuum degree involved in step S3 is 1.0×10 -3 Pa, the vacuum degree of step S4 and step S8 was maintained at 4.50×10 -3 Except that the constant temperature of step S5 is 5 min, the rest is the same as that of embodiment 1.

[0118] Example 3

[0119] Except for the vacuum degree of 5.0×10 -3 Pa, the vacuum degree involved in step S3 is 2.0×10 -3 Pa, the vacuum degree of step S4 and step S8 was maintained at 5.5×10 -3 Except that the constant temperature of step S5 is 15 min, the rest is the same as in Example 1.

[0120] Comparative Example 1

[0121] Except that in step S4, no ion source assisted deposition is used for the eighteen film layers, and in step S8, no ion source assisted deposition is used for the six film layers, the rest is the same as in embodiment 1.

[0122] Comparative Example 2

[0123] Except that the first layer in step S4 is a ZnSe film with a thickness of 100 nm and the first layer in step S8 is a ZnSe film with a thickness of 100 nm, the rest is the same as in Example 1. That is, in Comparative Example 1, only the first layers on both sides of Example 1 are replaced with ZnSe films with different film thicknesses.

[0124] Comparative Example 3

[0125] Except that the eighteenth layer in step S4 is a YbF3 layer with a thickness of 100.98 nm and the sixth layer in step S8 is a YbF3 layer with a thickness of 116.49 nm, the rest is the same as in Example 1. That is, in Comparative Example 1, only the outermost layers on both sides of Example 1 are replaced with YbF3 layers with the same thickness.

[0126] In accordance with GJB2485A-2019, the following tests were performed on both sides of Examples 1-3 and Comparative Examples 1-3 after coating.

[0127] Water bubble test: Take tap water to conduct a water bubble test for 2 hours to observe whether the film layer on each surface falls off from the accompanying plating sheet and whether the film layer on each surface is cracked.

[0128] Salt spray test: neutral salt spray test for 48 hours, observe whether the film layer on each side of the accompanying plating sheet falls off, observe whether the film layer on each side of the accompanying plating sheet cracks.

[0129] Adhesion test: After the blister or salt spray test with tap water is completed, stick 3M tape on each side of the PCB by hand and pull the tape in the direction opposite to the sticking end to observe whether the film layer is pulled up.

[0130] The blister test and the tape adhesion test can be used to determine whether the film adhesion on both sides of the plating sheet is good.

[0131] Thermal shock test: In a high and low temperature box, perform thermal shock test in the range of -40℃ to 85℃ for 24 hours to observe whether the film layers on each side of the accompanying plating sheet fall off or crack.

[0132] Constant temperature and humidity test: In a constant temperature and humidity chamber, at 50°C and 95% relative humidity for 48 hours, observe whether the film layers on each side of the accompanying plating sheet fall off or crack.

[0133] Low temperature test: In a low temperature box, at -40℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet fall off, and observe whether the film layers on each side of the accompanying plating sheet crack.

[0134] High temperature test: In a high temperature box, at 85℃ for 48h, observe whether the film layers on each side of the accompanying plating sheet fall off, and observe whether the film layers on each side of the accompanying plating sheet crack.

[0135] Figure 2 It is a reflectivity curve at 1064nm of the dual-frequency optical film coated with the accompanying coating sheet of Example 1, which reflects 1064nm wavelength and transmits 7.7-10.5μm band. Figure 3 It is a transmittance curve in the 7.7-10.5 μm band of the dual-frequency optical film coated with the accompanying coating sheet of Example 1, which reflects the 1064 nm wavelength and transmits the 7.7-10.5 μm band.

[0136] Figure 4 This is a reflectivity curve at 1064nm of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 2, which is plated on both sides of the accompanying plate. Figure 5 It is a transmittance curve diagram of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of Example 2, which is plated on both sides of the accompanying plate with zinc sulfide substrate in the 7.7-10.5μm band.

[0137] Figure 6 This is a reflectivity curve at 1064nm of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 3, which is plated on both sides of the accompanying plate. Figure 7 It is a transmittance curve diagram of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of Example 3, which is plated on both sides of the accompanying plate with zinc sulfide substrate in the 7.7-10.5μm band.

[0138] Figure 8 It is a reflectivity curve of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 1 coated on both sides of the accompanying coating sheet at a wavelength of 1064nm. Fig. 9 It is a transmittance curve of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of the accompanying coating sheet of comparative example 1, which is coated on both sides of the zinc sulfide substrate in the 7.7-10.5μm band.

[0139] Fig.10 This is a reflectivity curve of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 2, which is plated on both sides of the accompanying plate. Fig.11 It is a transmittance curve of the 7.7-10.5 μm band antireflection film system of the 1064 nm wavelength high-reflection 7.7-10.5 μm band of the accompanying coating sheet of Example 2, which is plated on both sides of the zinc sulfide substrate.

[0140] Fig.12 This is a reflectivity curve of the 1064nm wavelength high-reflective 7.7m-10.5μm band anti-reflection film system of Example 3, which is plated on both sides of the accompanying coating sheet with zinc sulfide substrate. Fig.13It is a transmittance curve of the 1064nm wavelength high-reflective 7.7-10.5μm band anti-reflection film system of the accompanying coating sheet of comparative example 3, which is coated on both sides of the zinc sulfide substrate in the 7.7-10.5μm band.

[0141] Table 1 shows the reflectivity (at a wavelength of 1064 nm), average transmittance (at a wavelength of 7.7-10.5 μm) of Examples 1-3 and Comparative Examples 1-3, and the results of various tests.

[0142] Table 1 Reflectivity, average transmittance and various test results of Examples 1-3 and Comparative Examples 1-3

[0143]

[0144]

[0145] As can be seen from Examples 1-3, the reflectivity of Examples 1-3 at a wavelength of 1064nm is more than 99%, the average transmittance in the 7.7-10.5μm band is more than 97.3%, and the blister test, salt spray test, adhesion test, hot and cold shock test, constant temperature and humidity test, low temperature test, and high temperature test are all passed.

[0146] The plating on both sides of Comparative Example 1 did not use ion source assisted deposition. The reflectivity of Comparative Example 1 at a wavelength of 1064nm exceeded 99%, and the average transmittance in the 7.7-10.5μm band also exceeded 97.3%, but the blister test failed. The remaining salt spray test, adhesion test, hot and cold shock test, constant temperature and humidity test, low temperature test, and high temperature test were no longer tested.

[0147] Comparative Example 2 uses ZnSe film material as the base. The average transmittance of Comparative Example 2 in the 7.7-10.5μm band exceeds 97.3%, but the reflectivity at the 1064nm wavelength is less than 99%. However, it fails the blister test, and the remaining salt spray test, adhesion test, hot and cold shock test, constant temperature and humidity test, low temperature test, and high temperature test are no longer tested.

[0148] The eighteenth layer in step S4 of comparative example 3 is a YbF3 film layer with a film thickness of 100.98 nm, and the sixth layer in step S8 is a YbF3 film layer with a film thickness of 116.49 nm. The reflectivity of comparative example 3 at a wavelength of 1064 nm exceeds 99%, but the average transmittance in the 7.7-10.5 μm band is lower than 97.3%. The blister test, adhesion test, and hot and cold shock test are all passed, but the constant temperature and humidity test is failed, and the salt spray test, low temperature test, and high temperature test are no longer tested.

[0149] The above detailed description is used to describe multiple exemplary embodiments, but this document is not intended to be limited to the explicitly disclosed combinations. Therefore, unless otherwise stated, the various features disclosed herein can be combined together to form multiple additional combinations that are not shown for the sake of simplicity.

Claims

1. A method for preparing a dual-frequency optical film with a zinc sulfide substrate that reflects 1064 nm wavelength and transmits 7.7-10.5 μm, characterized in that: Includes steps: S1, before plating, clean the accompanying plating sheet and products of the zinc sulfide substrate as the lens and prepare the two film materials of YbF3 and ZnSe; S2, the cleaned lens is placed in a fixture, and the fixture with the lens is hung in the cavity of the coating machine for vacuum baking and pre-melting of the film material; S3, ion source cleaning lens; S4, under vacuum conditions, on the first surface of the lens, a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer, a sixth ZnSe film layer, a seventh YbF3 film layer, an eighth ZnSe film layer, a ninth YbF3 film layer, a tenth ZnSe film layer, an eleventh YbF3 film layer, a twelfth ZnSe film layer, a thirteenth YbF3 film layer, a fourteenth ZnSe film layer, a fifteenth YbF3 film layer, a sixteenth ZnSe film layer, a seventeenth YbF3 film layer, and an eighteenth ZnSe film layer are deposited in sequence, the eighteen film layers forming a high-reflection film system, and the eighteen film layers are all deposited using an ion source as an auxiliary. S5, constant temperature maintenance after plating; S6, cooling and picking up; S7, repeating steps S1 to S3; S8, under vacuum conditions, sequentially depositing a first YbF3 film layer, a second ZnSe film layer, a third YbF3 film layer, a fourth ZnSe film layer, a fifth YbF3 film layer, and a sixth ZnSe film layer on the second surface of the lens, wherein the six film layers constitute an antireflection film system, and the six film layers are all deposited using an ion source to assist deposition; S9, repeat step S5 and step S6.

2. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S1, Cleaning is done by ultrasonic cleaning; The thickness of the accompanying plating sheet is 1.0 mm.

3. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S2, The temperature of the coating machine chamber is set to 150°C; When the vacuum reaches (3.0-5.0)×10 -3 The film material is pre-melted at Pa. After the pre-melting of the film material is completed, the temperature of the cavity of the coating machine reaches 150°C and is kept constant for 15-20 minutes.

4. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S3, When the vacuum degree reaches (1.0-2.0)×10 -3 Pa, start the ion source of the vacuum coating machine, The ion cleaning parameters of the ion source were set as follows: neutralization current 0.6 A, neutralization gas flow rate 8 sccm, anode voltage 220 V, anode current 2 A, argon flow rate in neutralization gas 100%, and cleaning time 250-350 s.

5. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S4 and step S8, During coating, argon gas is filled into the cavity of the coating machine and evacuated to form a flowing vacuum to ensure that the vacuum degree of the coating is maintained at (4.5-5.5)×10 -3 Pa, and maintain the coating temperature at 150°C.

6. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S4 and step S8, The evaporation mode of the film material is: both YbF3 and ZnSe are evaporated using resistance heating.

7. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S4 and step S8, The deposition rate of the film material is: The deposition rate of the YbF3 film layer is The deposition rate of ZnSe film is 8. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S4, The thickness of the first YbF3 film is 171.42±3nm. The thickness of the second ZnSe film is 341.29±3nm. The thickness of the third YbF3 film is 215.73±3nm. The thickness of the fourth ZnSe film is 84.31±3nm. The thickness of the fifth YbF3 film is 235.46±3nm. The thickness of the sixth ZnSe film layer is 320.79±3nm. The thickness of the seventh YbF3 film is 878.52±3nm. The thickness of the eighth ZnSe film layer is 150.83±3nm. The thickness of the ninth YbF3 film is 141.02±3nm. The thickness of the tenth ZnSe film is 352.72±3nm. The thickness of the eleventh YbF3 film layer is 214.99±3nm. The thickness of the twelfth ZnSe film is 95.59±3nm. The thickness of the thirteenth YbF3 film layer is 208.44±3nm. The thickness of the fourteenth ZnSe film layer is 369.79±3nm. The thickness of the fifteenth YbF3 film is 95.67±3nm. The thickness of the sixteenth ZnSe film layer is 597.16±3nm. The thickness of the seventeenth YbF3 film layer is 1316.55±3nm. The thickness of the eighteenth ZnSe film layer is 100.98±3nm; In step S8, The thickness of the first YbF3 film is 120.00±3nm. The thickness of the second ZnSe film is 910.06±3nm. The thickness of the third YbF3 film is 223.53±3nm. The thickness of the fourth ZnSe film is 910.91±3nm. The thickness of the fifth YbF3 film is 114.25±3nm. The thickness of the sixth ZnSe film layer is 116.49±3nm; In step S4 and step S8, the crystal oscillator method is used to monitor the film thickness using the corresponding crystal oscillator pieces of the multiple crystal oscillator pieces of the crystal controller. After the ion source is cleaned, the crystal controller controls the new crystal oscillator pieces among the multiple crystal oscillator pieces to work accordingly, and the crystal oscillator frequency is not less than 6 MHz.

9. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S4 and step S8, The ion source parameters when depositing the YbF3 film layer are: neutralization current 0.6A, neutralization gas flow rate 8sccm, anode voltage 130V, anode current 1.3A, argon flow rate in neutralization gas 30%, oxygen flow rate in neutralization gas 70%; The ion source parameters when depositing the ZnSe film layer are: neutralization current 0.5A, neutralization gas flow rate 8sccm, anode voltage 100V, anode current 1A, and argon gas flow rate in the neutralization gas is 100%.

10. The method for preparing a dual-frequency optical film having a zinc sulfide substrate that reflects a wavelength of 1064 nm and transmits a wavelength of 7.7-10.5 μm according to claim 1, characterized in that: In step S5, after the plating is completed, the cavity is kept at a constant temperature of 150° C. for 5-15 minutes; In step S6, the door is opened to take out the items when the temperature drops below 100°C.